2020
DOI: 10.1021/jacs.0c03105
|View full text |Cite
|
Sign up to set email alerts
|

Modeling DNA-Strand Displacement Reactions in the Presence of Base-Pair Mismatches

Abstract: Toehold-mediated strand displacement is the most abundantly used method to achieve dynamic switching in DNA-based nanotechnology. An 'invader' strand binds to the 'toehold' overhang of a target strand and replaces a targetbound 'incumbent' strand. Hereby, complementarity of the invader to the single-stranded toehold provides the energetic bias of the reaction. Despite the widespread use of strand displacement reactions for realizing dynamic DNA nanostructures, variants on the basic motif have not been complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
115
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(128 citation statements)
references
References 52 publications
13
115
0
Order By: Relevance
“…The observed slowdown induced by mismatches at different positions for RNA TMSD is hence compatible with the kinetics of TMSD of DNA strands with mismatches that was previously studied computationally and experimentally [26,27,34]. The kinetics of the TMSD can be approximately modeled as a stochastic Markovian process consisting of transitions between states characterized by the number of bonds between respective strands.…”
Section: B Mismatch Effectssupporting
confidence: 82%
“…The observed slowdown induced by mismatches at different positions for RNA TMSD is hence compatible with the kinetics of TMSD of DNA strands with mismatches that was previously studied computationally and experimentally [26,27,34]. The kinetics of the TMSD can be approximately modeled as a stochastic Markovian process consisting of transitions between states characterized by the number of bonds between respective strands.…”
Section: B Mismatch Effectssupporting
confidence: 82%
“…The rate of DNA strand displacement reactions can be modulated over several orders of magnitude by introducing one or more mismatches between the input strand and the target duplex ( 48 , 60 ). Rational positioning of mismatches provides a useful control mechanism for competitive reaction networks ( 60 , 62 ) and enables the design of strand displacement-based nucleic acid probes having a high-degree of mismatch discrimination ( 63 , 64 ). A common practical application is the detection of single nucleotide polymorphisms (SNPs), which are of great diagnostic value ( 65–67 ).…”
Section: Resultsmentioning
confidence: 99%
“…A series of inputs containing mismatches at a single position (and one input containing two mismatches within the toehold binding domain) were generated from input strand ( d -IN TH 8) having an 8-nucleotide toehold domain (Figure 3A ). Placement of the mismatches were, in part, informed by previous literature on the effects of mismatches on rates of all-DNA strand displacement reactions, as well as PNA–DNA hybridization ( 48 , 58 , 62 , 63 ).…”
Section: Resultsmentioning
confidence: 99%
“…Fourth, this metal-ligand complexation mediated strand displacement was also highly sensitive to the mismatched nucleotide in the invaded duplex structure through an asymmetric way as previously observed in the conventional toehold mediated Please do not adjust margins Please do not adjust margins displacement (Figure 4d). 56 Taken together, we revealed that the strand invasion by the metal-ligand complexation also possessed the efficiency, specificity, tunability and sensitivity similarly as the Watson-Crick base-paired toehold DNA, which could potentially achieve all kinds of dynamic stranddisplacement processes like a conventional toehold. Notably, compared with the Watson-Crick base-paired toehold, the metal-ligand paired toehold can present a unique feature of controllability during the dynamic strand displacement.…”
Section: S S Smentioning
confidence: 75%